2019
DOI: 10.1186/s13018-019-1535-9
|View full text |Cite
|
Sign up to set email alerts
|

The factors driving self-efficacy in intractable chronic pain patients: a retrospective study

Abstract: BackgroundThe fear-avoidance model is a theoretical paradigm for explaining acute and chronic pain. In this model, pain catastrophizing plays an important role. On the other hand, self-efficacy influences whether patients view their pain optimistically, ultimately preventing the conversion of pain into intractable pain. The aim of the present study was to evaluate the factors that influence self-efficacy in patients with chronic pain.MethodsStudy participants included 147 outpatients (35 men, 112 women) with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…This may have been due to the fact that 63.2% of the women in our study were already engaged in treatment for POP and so were not a naive sample, having already been exposed to strategies to improve their self‐efficacy 46 . Catastrophizing and poor self‐efficacy can exist independently of each other, which may explain the difference in the strength of the relationship of catastrophizing and self‐efficacy as predictors of bother 47 . Self‐efficacy strongly underpins motivation to adhere to pelvic floor training programs 46 so screening for, and implementation of specific strategies to improve low self‐efficacy, may ultimately improve outcomes of conservative management.…”
Section: Discussionmentioning
confidence: 95%
“…This may have been due to the fact that 63.2% of the women in our study were already engaged in treatment for POP and so were not a naive sample, having already been exposed to strategies to improve their self‐efficacy 46 . Catastrophizing and poor self‐efficacy can exist independently of each other, which may explain the difference in the strength of the relationship of catastrophizing and self‐efficacy as predictors of bother 47 . Self‐efficacy strongly underpins motivation to adhere to pelvic floor training programs 46 so screening for, and implementation of specific strategies to improve low self‐efficacy, may ultimately improve outcomes of conservative management.…”
Section: Discussionmentioning
confidence: 95%
“…It has been found that the reduction of kinesiophobia before and after lumbar surgery is linked to an increase in self-efficacy, 47 and that there is a positive relationship between self-efficacy and disability in patients with chronic pain and postoperative cardiac patients. 48 , 49 Du et al 50 argue that fear-avoidance belief is a risk factor for QOL and self-efficacy is a protective factor. As far as I could find, no research has shown that activity avoidance beliefs coexist with self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the standard analgesic titration protocols using oxycodone or morphine showed no significant difference in analgesic effects (9,22,23). However, another randomized controlled study showed that oxycodone sustained-release tablets had a superior time-to-analgesia onset compared to immediaterelease morphine, which helped to reduce titration (25,26). In our current study, the proportion of multiple BTP episodes was significantly lower in the oxycodone group than in the morphine group, which might be explained by the higher proportion of decreased NRS score in the oxycodone group.…”
Section: Discussionmentioning
confidence: 99%
“…In our current study, the proportion of multiple BTP episodes was significantly lower in the oxycodone group than in the morphine group, which might be explained by the higher proportion of decreased NRS score in the oxycodone group. Since early analgesia may increase the patient's pain threshold and thus reduce the patient's pain perception, it may achieve better pain relief and improve the patient's quality of life (25,26). In our current study, the ESAS score, which reflects the quality of life, was significantly lower in the oxycodone group than in the morphine group at the 24th hour (P=0.047), and the decrease of ESAS score was significantly larger in the oxycodone group (P<0.001), suggesting the oxycodone group had higher quality of life than the morphine group.…”
Section: Discussionmentioning
confidence: 99%